The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1021/la9711286
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Polystyrene Using Nitrogen Plasma. An X-ray Photoelectron Spectroscopy Study

Abstract: A detailed X-ray photoelectron spectroscopy study of a plasma-modified polystyrene (PS) surface was carried out after N2 plasma treatment. PS surfaces were found to be highly hydrophilic and reactive as it readily picks up oxygen giving rise to oxyfunctionalities on the surface. The plasma treatment also led to a slow chain scission with carboxyl, forming carbonate linkage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 20 publications
4
54
0
Order By: Relevance
“…The presence of functional groups and chemical status of elements, rough and smooth surface, hydrophobic and hydrophilic properties of materials was characterized by using X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), and water contact angle (WCA) measurements (North et al 2010;Qin et al 2007;Idage and Badrinarayanan 1998). However, these characterization methods are cost-effective, time consuming and they are not affordable for routine modification process in the view of commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of functional groups and chemical status of elements, rough and smooth surface, hydrophobic and hydrophilic properties of materials was characterized by using X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), and water contact angle (WCA) measurements (North et al 2010;Qin et al 2007;Idage and Badrinarayanan 1998). However, these characterization methods are cost-effective, time consuming and they are not affordable for routine modification process in the view of commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…For PS surface with CA of 76°, a rough surface of micro/nano pillars-aligned patterns may make it hydrophobic according to Cassie state (no-wetted state). It is well known that plasma irradiation change the chemical composition of PS surface [40][41][42] to lead to a slow chain scission with hydroxyl group, carboxyl group, are discussed in references in detail [26,43,44]. If PS surface or coating was treated using air plasma irradiation, the hydrophilic surface with CA of 15° was obtained.…”
Section: Wettability Transition From Hydrophobicity To Hydrophilicitymentioning
confidence: 99%
“…As demonstrated previously for the plasma treatment, the oxygen detected on the treated surface is due to contamination following reaction of unsaturated bonds on the surface with the ambient air during transfer of the sample from the treatment chamber to the XPS spectrometer. 7,9,17,20 It is also demonstrated elsewhere 21 that in situ ionic bombardment produces only nitrogen grafted on the surface. In this case, no oxygen is detected because the treated sample never returns to atmospheric pressure before XPS analysis.…”
Section: Resultsmentioning
confidence: 93%
“…In some of the numerous previous studies 17,19 on polystyrenes treated by nitrogen plasma it was shown that, for a 60 s long discharge, an N/C ratio of 0.01 accompanied by an O/C ratio of 0.34 is obtained 17 and a maximum N/C ratio of 0.12 is obtained with the optimal conditions in a microwave plasma on PS powders after a 20 min treatment. 19 We thus conclude that the Kaufman source is able to incorporate a similar amount of heteroatoms as the plasma treatment did in the two particular cases quoted, and this in a much shorter time (65 s, see Fig.…”
Section: Resultsmentioning
confidence: 96%